Range of motion evaluation of the patients after total shoulder arthroplasty in Dr. Saiful Anwar general hospital: case series - Pratianto, Arimurti; Santoso, Agung R. B.; Wijaya, Anindita (International Journal of Research in Medical Sciences, 2019)
The hemiarthroplasty is most commonly used after a fracture or musculoskeletal tumor of the shoulder where the blood supply to the ball portion (the humeral head) of the humerus is damaged. Since then, hemiarthoplasty has been used in many shoulder diseases including osteoarthritis, avascular necrosis, rheumatoid arthritis, cuff-tear arthropathy, and fracture sequele. Methods are authors evaluated 2 patients who had shoulder hemiarthroplasty on October 2017. The first patient is 53-year-old male, surgery due to primary bone tumor right proximal humerus suspected chondrosarcoma and the second is 72-year-old female with closed fracture dislocation of left glenohumeral joint after traffic accident. The patients followed up until 2 years and get routine medical rehabilitation on outpatients’ workup. ROM of shoulder joints which had operated evaluated 2 years post-operative. Results are First patient, active ROM extension is 20o, flexion is 10o, abduction is 30o, adduction is 20o, external rotation is 10o, internal rotation is 40o, while passive ROM extension is 150o, flexion is 30o, abduction is 110o, adduction is 40o, external rotation is 30o while internal rotation is 50o. Second patient, active ROM extension is 60o, flexion is 20o, abduction is 40o, adduction is 40o, external rotation is 20o, internal rotation is 60o, while passive ROM extension is 10o, flexion is 45o, abduction is 160o, adduction is 45o, external rotation is 30o while internal rotation is 80o. Conclusions are Careful and long-term post-operative care including Rehabilitation plays an important role in functional outcomes after Shoulder hemiarthroplasty.